PENGARUH REKRUTMEN, KOMPENSASI TERHADAP KINERJA SATUAN PENGAMANAN DILINGKUNGAN KELURAHANAN CEMPAKA PUTIH TIMUR - Zahera Mega Utama (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The title of this research is the influence of the recruitment process, compensation on the performance of security unit personnel in the Cempaka Putih Timur Village Area. This study aims: 1) To determine the effect of the recruitment process on security guard performance 2) To determine the effect of compensation on performance. 4) To determine the effect of the recruitment process, compensation, on performance The method used in this research is descriptive method and the type of correlational study. The approach used in this research is a quantitative approach. In this study, the authors took samples using a non-probability sampling method, which is a method that is not based on a random mechanism in the selection of research samples. The conclusion from the results of the analysis that has been carried out, it can be concluded that the results of the regression coefficient analysis on the constant variable (a), it is known that it is 4.552, while X1 (recruitment) is 0.879, while X2 (compensation) is 0.630, thus it can be said that X2 (compensation) which experienced the lowest increase. The results of the joint test through the F test, it is known that the value of Fcount 27.129 F table 3.16, thus it can be said that recruitment and compensation carried out together significantly affect employee performance. The results of individual testing through the T test, it is known that the Tcount of recruitment (X1) is 2.174 T table 2.003, then H0 is rejected and Ha is accepted. While the value of Tcount compensation (X2) 2.242 T table 2.003, then H0 is rejected and Ha is accepted. The test results of the Coefficient of Determination, R Square, are 0.492 = 49.2%, while the rest is 50.8%. From this value it can be seen that employee performance is influenced by recruitment and compensation by 53.4%. Keywords: recruitment, compensation, performance.